Genetic Diversity and Population Structure of Vibrio parahaemolyticus Isolated From Clinical and Food Sources - Min He; Min He; Tao Lei; Fufeng Jiang; Fufeng Jiang; Jumei Zhang; Haiyan Zeng; Juan Wang; Moutong Chen; Liang Xue; Shi Wu; Qinghua Ye; et al. (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus is a common foodborne pathogen that causes gastroenteritis worldwide. Determining its prevalence and genetic diversity will minimize the risk of infection and the associated economic burden. Multilocus sequence typing (MLST) is an important tool for molecular epidemiology and population genetic studies of bacteria. Here, we analyzed the genetic and evolutionary relationships of 162 V. parahaemolyticus strains isolated in the Guangdong Province, China, using MLST. In the study, 120 strains were isolated from food samples, and 42 strains were isolated from clinical samples. All strains were categorized into 100 sequence types (STs), of which 58 were novel (48 from the food isolates and 10 from the clinical isolates). ST415 was the most prevalent ST among the food isolates, while ST3 was the most prevalent ST among the clinical isolates. Further, 12 clonal complexes, 14 doublets, and 73 singletons were identified in all ST clusters, indicating high genetic diversity of the analyzed strains. At the concatenated sequence level, non-synonymous sites in both, food and clinical isolates, were associated with purifying selection. Of note, the dN/dS ration was greater than 1 for some housekeeping genes in all isolates. This is the first time that some loci under positive selection were identified. These observations confirm frequent recombination events in V. parahaemolyticus. Recombination was much more important than mutation for genetic heterogeneity of the food isolates, but the probabilities of recombination and mutations were almost equal for the clinical isolates. Based on the phylogenetic analysis, the clinical isolates were concentrated in the maximum-likelihood tree, while the food isolates were heterogeneously distributed. In conclusion, the food and clinical isolates of V. parahaemolyticus from the Guangdong Province are similar, but show different evolutionary trends. This may help prevent large-scale spread of highly virulent strains and provides a genetic basis for the discovery of microevolutionary relationships in V. parahaemolyticus populations.